Vipassanā Meditation in Contemporary Psychiatry: Transformation of a Buddhist Practice into a Mental Health Intervention - Dimas Andri Wijaya; Anna Miharti; Meilisa Ratnawati; Yuly Dahlia (Yayasan Albahriah Jamiah Indonesia, 2026)
The integration of meditation practices into contemporary psychiatry reflects a shift from a reductionistic biomedical model to a more holistic approach to mental health. However, the epistemological transformation of Buddhist practices such as Vipassanā into a secular-psychological framework still leaves conceptual and methodological problems that have not been critically and comprehensively examined. This article aims to systematically analyze the epistemological transformation of Vipassanā from a soteriological framework to an evidence-based clinical paradigm, evaluate the level and quality of its clinical validity in the treatment of depression, anxiety, and stress, identify the underlying psychological mechanisms, and formulate challenges for its integration into psychiatric practice. The study used Critical Interpretive Synthesis with an inclusion-exclusion protocol for empirical articles and international meta-analyses indexed in PubMed and Scopus for the period 2000–2025, which were analyzed using a thematic-critical synthesis approach. The results indicate the occurrence of normative reduction and conceptual recontextualization, primarily through the elimination of ethical-doctrinal dimensions of achieve empirical compatibility. Clinically, the majority of randomized controlled trials and meta-analyses report moderate and consistent effects on reducing symptoms of depression and anxiety, although heterogeneity in design and sample size limits generalizability. Identified mechanisms include improved attentional regulation, cognitive decentralization, decreased affective reactivity, and enhanced executive function and metacognitive awareness. Key challenges include excessive decontextualization, methodological inconsistencies, and ethical issues surrounding the appropriation of contemplative practices. These findings underscore the need for a reflective, integrative theoretical framework to strengthen interdisciplinary dialogue and enhance the rigor of evidence-based clinical implementation of meditation in psychiatry.